Analisis Resiko Bencana Kekeringan di Lombok Tengah Sebagai Upaya Mitigasi Bencana - Lalu Ahmad Murdhani; Mujahidin Mujahidin; Fanila Kasmita; Marzuki Marzuki (IPDN Kampus NTB, 2024)
This research focuses on analyzing the risk of drought disasters in Central Lombok Regency for disaster management and mitigation purposes that can be implemented in the future. This disaster risk analysis has been prepared using a methodology adapted to the Regulation of the Head of the National Disaster Management Agency Number 02 of 2012 concerning General Guidelines for Disaster Risk Analysis, as well as referring to other guidelines applicable at national level ministries/institutions. From the results of the drought disaster risk analysis that has been carried out, it can be concluded that most of the Central Lombok district is in the Red Zone against the threat of drought, especially in the eastern, central, city, western and southern regions, only a few areas in the northern part of Central Lombok which is in the Green Zone. The results of this research show that the highest risk of drought disaster is in Pujut District which has the largest land area in the red zone, namely 18,832 Ha of land or the equivalent of 81.88% of its entire area. This makes Pujut sub-district the area that experiences the most drought disasters.